Economic implications of socio-economic inequalities in health in the European Union - Mackenbach, Johan P.; Meerding, Willem-Jan; Kunst, Anton E. (Brussels, 2007)
"Most analyses of the relationship between health and the economy focus on average health, but health is actually very unevenly distributed across society. In all countries with available data, significant differences in health exist between socioeconomic groups, in the sense that people with lower levels of education, occupation and/or income tend to have systematically higher morbidity and mortality rates. These health inequalities are one of the main challenges for public health, and there is a great potential for improving average population health by eliminating or reducing the health disadvantage of lower socioeconomic groups. This requires an active engagement of many policy sectors, not only of the public health and health care systems, but also of education, social security, working life, city planning, etcetera. A fruitful dialogue between the public health and health care sector on the one hand, and other policy areas on the other hand, is likely to be facilitated if the economic benefits of reducing health inequalities were be made clear. It is the purpose of this report to explore the economic implications of health inequalities in the European Union. It addresses four specific questions. Firstly, how should we conceptualize the ‘economic impact’ of socioeconomic inequalities in health, and how can we measure this? Secondly, how large are socioeconomic inequalities in health in the European Union, and what is the magnitude of the burden of ill health and premature mortality associated with inequalities in health? Thirdly, what is the economic impact of socioeconomic inequalities in health in the European Union? And finally, what actions can reasonably be taken to reduce socioeconomic inequalities in health, and what are the potential economic benefits of investing in these strategies? ..."